2017
DOI: 10.1617/s11527-017-1002-1
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of the RILEM round robin on degree of reaction of slag and fly ash in blended cements

Abstract: This is a repository copy of Outcomes of the RILEM round robin on degree of reaction of slag and fly ash in blended cements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(47 citation statements)
references
References 17 publications
3
43
0
1
Order By: Relevance
“…The PONKCS results were shown to be in line with those of other independent techniques such as selective dissolution (for FA) (Durdziń ski et al, 2017), mass balance and thermodynamic modelling (for calcined clay) (Avet et al, 2018). Nevertheless, a round-robin study by RILEM (International Union of Laboratories and Experts in Construction Materials, Systems and Structures) committee TC SCM concluded that, in the absence of a clear analytical protocol, the PONKCS results for the degree of reaction of FA reported by the participants presented larger scatter than those of other techniques such as selective dissolution or back-calculation from portlandite consumption (Durdziń ski et al, 2017).…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…The PONKCS results were shown to be in line with those of other independent techniques such as selective dissolution (for FA) (Durdziń ski et al, 2017), mass balance and thermodynamic modelling (for calcined clay) (Avet et al, 2018). Nevertheless, a round-robin study by RILEM (International Union of Laboratories and Experts in Construction Materials, Systems and Structures) committee TC SCM concluded that, in the absence of a clear analytical protocol, the PONKCS results for the degree of reaction of FA reported by the participants presented larger scatter than those of other techniques such as selective dissolution or back-calculation from portlandite consumption (Durdziń ski et al, 2017).…”
Section: Introductionsupporting
confidence: 78%
“…The application of the method to hydrated systems was explored in some recent publications on slag, fly ash (FA), micro silica or calcined clay blended cements (Avet et al, 2018;Bhagath, Singh & Subramaniam, 2016;Snellings, Salze & Scrivener, 2014;Zajac et al, 2018;Naber et al, 2019), and alkali-activated materials (Sun & Vollpracht, 2018). The PONKCS results were shown to be in line with those of other independent techniques such as selective dissolution (for FA) (Durdziń ski et al, 2017), mass balance and thermodynamic modelling (for calcined clay) (Avet et al, 2018). Nevertheless, a round-robin study by RILEM (International Union of Laboratories and Experts in Construction Materials, Systems and Structures) committee TC SCM concluded that, in the absence of a clear analytical protocol, the PONKCS results for the degree of reaction of FA reported by the participants presented larger scatter than those of other techniques such as selective dissolution or back-calculation from portlandite consumption (Durdziń ski et al, 2017).…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Granulowany żużel wielkopiecowy jest dodatkiem o utajnionych właściwościach hydraulicznych, tzn. aktywowany wiąże i twardnieje zarówno w środowisku wodnym, jak i na powietrzu, z utworzeniem produktów o właściwościach hydraulicznych [9][10][11][12][13]. Aktywatorami mielonych granulowanych żużli wielkopiecowych mogą być: związki zasadowe lub słabo kwaśne; oddziaływania fizyczne, np.…”
Section: Wprowadzenieunclassified
“…The extents of reaction of blast furnace slag and fly ashes in practical cementitious blends (w/c 0.40; replacement levels 30-40%) have been determined by multiple techniques in a recent RILEM round robin test [17]; at 90 d, slag had reacted around 40-50% and fly ashes 20-30%. According to the literature survey of Zeng et al [18], the extent of cement hydration at this age and w/c ratio would be expected to be around 70-80%.…”
Section: Consequences Recommendations and 4 Conclusionmentioning
confidence: 99%